Ultra-Stable Sodium-Ion Battery Enabled by All-Solid-State Ferroelectric-Engineered Composite Electrolytes - Wang, Yumei; Wang, Zhongting; Xu, Xiaoyu; Oh, Sam Jin An; Sun, Jianguo; Zheng, Feng; Lu, Xiao; Xu, Chaohe; Yan, Binggong; Huang, Guangsheng; Lu, Li (Nano-Micro Letters, 2024)
Symmetric Na-ion cells using the NASICON-structured electrodes could simplify the manufacturing process, reduce the cost, facilitate the recycling post-process, and thus attractive in the field of large-scale stationary energy storage. However, the long-term cycling performance of such batteries is usually poor. This investigation reveals the unavoidable side reactions between the NASICON-type Na3V2(PO4)3 (NVP) anode and the commercial liquid electrolyte, leading to serious capacity fading in the symmetric NVP//NVP cells. To resolve this issue, an all-solid-state composite electrolyte is used to replace the liquid electrolyte so that to overcome the side reaction and achieve high anode/electrolyte interfacial stability. The ferroelectric engineering could further improve the interfacial ion conduction, effectively reducing the electrode/electrolyte interfacial resistances. The NVP//NVP cell using the ferroelectric-engineered composite electrolyte can achieve a capacity retention of 86.4% after 650 cycles. Furthermore, the electrolyte can also be used to match the Prussian-blue cathode NaxFeyFe(CN)6−z·nH2O (NFFCN). Outstanding long-term cycling stability has been obtained in the all-solid-state NVP//NFFCN cell over 9000 cycles at a current density of 500 mA g−1, with a fading rate as low as 0.005% per cycle. Highlights: 1 The capacity fading mechanism of the conventional Na3V2(PO4)3//Na3V2(PO4)3 (NVP//NVP) cell has been investigated. 2 All-solid-state ferroelectric-engineered composite electrolyte could improve the electrolyte–electrode interfacial stability as well as the interfacial ion conduction of the Na-ion battery using the NVP anode. 3 Outstanding cyclic stability has been achieved in the all-solid-state Na-ion battery using the NVP anode, with a capacity fading rate as low as 0.005% per cycle.